Size mismatch in deceased donor liver transplantation and its impact on graft survival. Issue 8 (26th July 2019) - Reyes, Jorge; Perkins, James; Kling, Catherine; Montenovo, Martin
Abstract: The impact of size mismatch in deceased donor liver transplantation is unknown. BSA has been demonstrated to be an accurate indicator of liver volume. We developed a model to match livers by BSA and estimate the impact of size mismatch on graft survival. Using the Standard Transplant Analysis and Research (STAR) database we selected solitary primary liver transplants recipients of any age, transplanted between 3/6/2002 and 12/31/2016. Using the Cox proportional hazard model, and controlling for donor and recipient factors, we determined the relative risk for graft survival for four donor/recipient body surface area ratio groups (≤0.68, 0.69‐0.90, 0.91‐1.25, 1.26‐1.5). We studied two groups: recipients with a BSA > 1.6 (adults) and ≤1.6 (children) and a subgroup with a BSA ≤ 0.53 (small infants). In recipients with BSA > 1.6 (adults [n = 71 365]), D/R ratios ≤ 0.68 and > 1.25 had a negative impact on graft survival. In recipients with BSA ≤ 1.6 (children [n = 8339]) D/R ratios <0.75 and >1.25 had a negative impact on graft survival. In the 1725 recipients with BSA ≤ 0.53 (small infants) D/R ratios <1 and >2.3 had a negative impact on graft survival. In deceased donor liver transplantation, the D/R ratio is a significant, yet underestimated predictor of graft survival that should be considered in donor and recipient selection.